Expressing the Extreme-Thermostable Xylanase B64 with Different Fusion Tags - Shen, N.; Bai, Y.; Sun, T.; Jiang, H.Y.; Wei, P. (Asian Journal of Chemistry, 2012)
Xylanase B from thermophile bacteria Thermotoga maritima MSB8 was extreme-thermostable and has potential application for feed, paper manufacture, energy, food and medicine industries. Recombinant plasmid pET28a (+)-xynB64 was induced and expressed in E. coli BL21 (DE3) and the activity of recombinant enzyme xylanase was very low. Both E. coli BL21-CodonPlus (DE3)-RIPL and Rosetta (DE3) possessing rare tRNAs were used to be the expressing host and the activity of recombinant enzyme increased by 197 % and 277 %, respectively. However, inclusion body was formed in E. coli Rosetta (DE3). The next step, pET32a (+), pET42a (+), pET43.1a (+) and pMAL-c2X, which contain the Trx, GST, Nus and MBP fusion tag respectively were used to be the expression vector with E. coli Rosetta (DE3) as the host. The activity of recombinant enzyme produced by Rosetta (DE3)/pMAL-c2X-xynB64 was the highest, which was equivalent to 88 % of counterparts of Rosetta (DE3)/pET28a-xynB64. Meanwhile about 40 % whole cell proteins of former were recombinant XynB64 with little inclusion body.